Coupled behavior of shape memory alloy-based morphing spacecraft radiators: experimental assessment and analysis. (3rd May 2018) - Bertagne, C; Walgren, P; Erickson, L; Sheth, R; Whitcomb, J; Hartl, D
Abstract: Thermal control is an important aspect of spacecraft design, particularly in the case of crewed vehicles, which must maintain a precise internal temperature at all times in spite of significant variations in the external thermal environment and internal heat loads. Future missions beyond low Earth orbit will require radiator systems with high turndown ratios, defined as the ratio between the maximum and minimum heat rejection rates achievable by the radiator system. Current radiators are only able to achieve turndown ratios of 3:1, far less than the 12:1 turndown ratio requirement expected for future missions. An innovative morphing radiator concept uses the temperature-induced phase transformation of shape memory alloy (SMA) materials to achieve turndown ratios that are predicted to exceed 12:1 via substantial geometric reconfiguration. Developing mathematical and computational models of these morphing radiators is challenging due to the strong two-way thermomechanical coupling not present in traditional fixed-geometry radiators and not widely considered in the literature. Although existing simulation tools are capable of analyzing the behavior of some thermomechanically coupled structures, general problems involving radiation and deformation cannot be modeled using publicly available codes due to the complexity of modeling spatially evolving boundary fields. This paper provides important insight into the operational response of SMA-based morphing radiators by employing computational tools developed to overcome previous shortcomings. Several example problems are used to demonstrate the novel radiator concept. Additionally, a prototype morphing radiator was designed, fabricated, and tested in a thermal environment compatible with mission operations. An associated finite element model of the prototype was developed and executed. Model predictions of radiator performance generally agree with the experimental data, giving confidence that the tools developed are able to accurately represent the thermomechanical coupling present in morphing radiators and that such tools will be useful in future designs.